Inactivation of Nell‐1 in Chondrocytes Significantly Impedes Appendicular Skeletogenesis. (14th December 2018) - Qi, Huichuan; Kim, Jong Kil; Ha, Pin; Chen, Xiaoyan; Chen, Eric; Chen, Yao; Li, Jiayi; Pan, Hsin Chuan; Yu, Mengliu; Mohazeb, Yasamin; Azer, Sophia; Baik, Lloyd; et al.
ABSTRACT: NELL‐1, an osteoinductive protein, has been shown to regulate skeletal ossification. Interestingly, an interstitial 11p14.1‐p15.3 deletion involving the Nell‐1 gene was recently reported in a patient with short stature and delayed fontanelle closure. Here we sought to define the role of Nell‐1 in endochondral ossification by investigating Nell‐1‐specific inactivation in Col2α1‐expressing cell lineages. Nell‐1 flox/flox ; Col2α1‐Cre + (Nell‐1 Col2α1 KO) mice were generated for comprehensive analysis. Nell‐1 Col2α1 KO mice were born alive but displayed subtle femoral length shortening. At 1 and 3 months postpartum, Nell‐1 inactivation resulted in dwarfism and premature osteoporotic phenotypes. Specifically, Nell‐1 Col2α1 KO femurs and tibias exhibited significantly reduced length, bone mineral density (BMD), bone volume per tissue volume (BV/TV), trabecular number/thickness, cortical volume/thickness/density, and increased trabecular separation. The decreased bone formation rate revealed by dynamic histomorphometry was associated with altered numbers and/or function of osteoblasts and osteoclasts. Furthermore, longitudinal observations by in vivo micro‐CT showed delayed and reduced mineralization at secondary ossification centers in mutants. Histologically, reduced staining intensities of Safranin O, Col‐2, Col‐10, and fewer BrdU‐positive chondrocytes were observed in thinner Nell‐1 Col2α1 KO epiphyseal plates along with altered distribution and weaker expression level of Ihh, Patched‐1, PTHrP, and PTHrP receptor. Primary Nell‐1 Col2α1 KO chondrocytes also exhibited decreased proliferation and differentiation, and its downregulated expression of the Ihh‐PTHrP signaling molecules can be partially rescued by exogenous Nell‐1 protein. Moreover, intranuclear Gli‐1 protein and gene expression of the Gli‐1 downstream target genes, Hip‐1 and N‐Myc, were also significantly decreased with Nell‐1 inactivation. Notably, the rescue effects were diminished/reduced with application of Ihh signaling inhibitors, cyclopamine or GANT61. Taken together, these findings suggest that Nell‐1 is a pivotal modulator of epiphyseal homeostasis and endochondral ossification. The cumulative chondrocyte‐specific Nell‐1 inactivation significantly impedes appendicular skeletogenesis resulting in dwarfism and premature osteoporosis through inhibiting Ihh signaling and predominantly altering the Ihh‐PTHrP feedback loop. © 2018 American Society for Bone and Mineral Research.